2020
DOI: 10.1002/cti2.1210
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeting of miR‐223 in experimental eosinophilic oesophagitis

Abstract: Objectives Eosinophilic oesophagitis (EoE) is characterised by oesophageal inflammation, fibrosis and dysfunction. Micro (mi)‐RNAs interfere with pro‐inflammatory and pro‐fibrotic transcriptional programs, and miR‐223 was upregulated in oesophageal mucosal biopsy specimens from EoE patients. The therapeutic potential of modulating miR‐223 expression in vivo has not been determined. We aimed to elucidate the relevance of oesophageal miR‐223 expression in an in vivo model of EoE by inhibiting miR‐223 tissue expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Consistent with both local and systemic immune mechanisms, a recent study demonstrated the local deposition of dust mite antigens in the esophageal epithelium of patients with EoE [32 & ,33 & ]. These data are consistent with animal models of EoE in which esophageal eosinophilia, T cell infiltration, and mastocytosis are driven by nasal challenge with aeroallergens such as house dust mite and aspergillus [34,35]. It should be noted that there is some controversy in the literature regarding seasonal aeroallergen effects on EoE.…”
Section: Key Pointssupporting
confidence: 84%
“…Consistent with both local and systemic immune mechanisms, a recent study demonstrated the local deposition of dust mite antigens in the esophageal epithelium of patients with EoE [32 & ,33 & ]. These data are consistent with animal models of EoE in which esophageal eosinophilia, T cell infiltration, and mastocytosis are driven by nasal challenge with aeroallergens such as house dust mite and aspergillus [34,35]. It should be noted that there is some controversy in the literature regarding seasonal aeroallergen effects on EoE.…”
Section: Key Pointssupporting
confidence: 84%
“…The depth of eosinophil infiltration into the esophagus is related to types of respiratory antigen and the exposure procedures. Simple respiratory allergenic (such as dog, cat, cockroach, dust mite and A. fumigatus) stimulation, lasting for 21–28 days, could promote the infiltration of eosinophil, mainly in the epithelium [ 12 , 25 ]. However, if the mice were sensitized by intraperitoneal injection of OVA and then exposed to OVA via respiratory tract for 24 days, the eosinophil infiltrated more deeply, with most of the eosinophils infiltrated into the mucosa and submucosa [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since AC-like dysmotility can also be seen in some eosinophilic esophagitis (EoE) patients [ 10 ], using an animal model of EoE as a surrogate is a potential solution. Among various methods to establish an animal model of EoE [ 11 , 12 , 13 , 14 ], the respiratory tract antigen, such as ovalbumin (OVA), exposure is simple, low cost and easy to control experimental conditions [ 15 ]. However, to the best of our knowledge, the depth of the eosinophil infiltration is mainly in squamous-epithelial, lamina propria and submucosa of esophagus in the mouse models listed above [ 11 , 14 , 15 ], which is not consistent with previous pathological finding in AC.…”
Section: Introductionmentioning
confidence: 99%